0077 Reconstruction of exposed cohort and cumulative dose of radio-contaminated building residents for epidemiological study - Updated information. (23rd June 2014) - Chiang, Shu-O; Chen, Chien-Hao; Tung, Chuan-Jong; Chou, Pesus; Whang-Peng, Jacqueline; Chiou, Hung-Yi; Chen, Chien-Jen; Chen, Yi-Hau; Yu, Li-Hui; Chang, Jang-Yang; Jyuhn-Hsiarn Lee, Lukas; Liou, Saou-Hsing
Abstract : Objectives: The purpose of this study is to reconstruct of RCB cohort and to survey occupancy factors for estimation of cumulative dose in study of health risk of Radio-contaminated building (RCB) occupants. Method: The cohort of RCB occupants was established based on household, school and labour registration. Survey of current and retrospective occupancy factors in each age stratum was conducted to estimate the cumulative dose. Risk-period adjusted cumulative dose was generated in this study. Results: There were totally 32 622 in this study cohort, including 13 120 residents of RCBs, 15 368 students in RCB schools, and 4328 labours in RCB business workplaces. The mean and maximal dose in the year of RCB built was 32.7 and 998.56 mSv, respectively (Table 2). The main difference between retrospective (RCB residents) and current (general population) occupancy factors was RCB residents in the past had 2 more hours in living room, while current general population had 2 more hours in bed room. When bedroom was subdivided into bed and desk, we found current general population had 2 more hours in the desk of bed room. In total, the mean cumulative dose was 7.06 mSv with range of 0–1751 mSv. The mean cumulative dose for residents, labours, and students were 16.08, 2.91, and 0.48 mSv, respectively. Conclusions: We have established a new RCB cohort and provided new information of cumulative dose estimation. These data could provide valid information on the risk of cancers and non-cancer diseases at low dose and low dose-rate radiation exposure.